The Growing Intergenerational Housing Wealth Divide: Drivers And Interactions In Australia. Issue 2 (15th March 2023) - Ong ViforJ, Rachel; Phelps, Christopher
ABSTRACT: This paper unpacks the drivers of growing intergenerational housing wealth inequality in Australia. We also account for the multidimensional nature of housing wealth divides by examining the interaction between age and other divides. We find that the Australian intergenerational housing wealth gap widened from 161% in 1997–98 to 234% in 2017–18, favouring the older cohort. This was driven by lower rates of homeownership and lower property value growth among younger cohorts, with the relative lack of homeownership access the more significant driver. However, higher rates of couple formation and tertiary education amongst the young mitigated a further widening of the gap. The intergenerational housing wealth gap is exacerbated within specific population subgroups. The growing housing wealth gap between the income-poor young and income-rich old has been particularly alarming, climbing from 532% to 1230% over two decades. We discuss implications for policies seeking to alleviate intergenerational tensions in housing markets.